2019
DOI: 10.1027/1016-9040/a000331
|View full text |Cite
|
Sign up to set email alerts
|

The Psychology of Euthanasia

Abstract: Abstract. Voluntary euthanasia has been legalized in several countries and associated with this development there has been much discussion concerning the relationship between the ethical principle of autonomy and the respect for human life. Psychological science should make a significant contribution to understanding how polarizing positions may be taken in such debates. However, little has been written concerning the implications of this research for the euthanasia debate and about the contributions of psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…If death ideation is commonly self-reported by patients as a response to suffering (Branigan, 2015), the same issue can be closely connected with those about the requests to hasten death. According to the results obtained in the literature review carried out by Ricou and Wainwright (2018), the main motivators of a wish to die are connected with patient suffering (e.g., pain) and the perception that patients have about the suffering they believe they cause others. The authors also identified important psychological dimensions that seem to be associated to the wish to die and argue about a possible role for the mental health professionals on this subject.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If death ideation is commonly self-reported by patients as a response to suffering (Branigan, 2015), the same issue can be closely connected with those about the requests to hasten death. According to the results obtained in the literature review carried out by Ricou and Wainwright (2018), the main motivators of a wish to die are connected with patient suffering (e.g., pain) and the perception that patients have about the suffering they believe they cause others. The authors also identified important psychological dimensions that seem to be associated to the wish to die and argue about a possible role for the mental health professionals on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Another problem frequently identified has to do with establishing a satisfactory temporal interval upon which to rely on for assessing will to die. Taking into consideration the psychological motivators identified in the wish to die (Ricou & Wainwright, 2018), this issue assumes particular relevance. The determination of said interval, even though in an estimated form, is an important complement to individual scale and marker evaluation as it could contribute to a more accurate assessment of wish to die and the likelihood of its endurance over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social euthanasia has its etymology rooted in euthanasia (good death) (Ricou & Wainwright, 2019). In euthanasia, the medic facing the dilemma caused by the terminally ill and the suffering due to the illnesses, decide to end the life of the patient.…”
Section: Misthanasia: Memorable Presence In Brazilian Healthmentioning
confidence: 99%
“…One of the most emergent topics of debate in modern societies is that of hastened death (Bulmer et al., 2017; Siden, 2005). Important arguments have been raised on both ends of the discussion (Math & Chaturvedi, 2012; Ricou & Wainwright, 2019), but the determinants of one’s standpoint in this matter have not been given full attention. An individual’s position in such matters should essentially be a complex end-product of personality traits, personal beliefs and environment.…”
mentioning
confidence: 99%